Enrichment of antibacterial compound from the stem bark of Stereospermum fimbriatum using supercritical carbon dioxide extraction - Awang, Anis Fadhlina Izyani; Sarker, Md Zaidul Islam; Ahmed, Qamar Uddin; Md. Jaffri, Juliana; Sheikh Mohamed, Hassan Ibrahim; Ferdosh, Sahena (Taylor and Francis, 2019)
Supercritical carbon dioxide (sc-CO2) extraction was carried out on Stereospermum fimbriatum’s stem bark in order to obtain an enriched extract containing the targeted active compound. The recovery of its active compound, C1, was compared with the most active Soxhlet’s extract of dichloromethane. A minimum inhibitory concentration (MIC) assay was done to examine the antibacterial activity of extracts against methicillin-resistant Staphylococcus aureus. The optimum condition for an enriched extract of sc-CO2 to have a maximum recovery of C1 at MIC value of 400 µg/mL was suggested to be operated at 40°C and pressure at 30 MPa, with addition of 6% co-solvent.